Theoretical analysis to determine the efficiency of a CuO-water nanofluid based-flat plate solar collector for domestic solar water heating system in Myanmar - Sint, N.K.C.; Choudhury, I.A.; Masjuki, Haji Hassan; Aoyama, H. (Elsevier, 2017)
The efficiency of a flat plate solar collector using water based CuO nanofluid as a working fluid is analyzed theoretically. A mathematical model and a program, written in MATLAB code were used for calculating the efficiency of a flat plate solar collector for a domestic solar water heating system considering weather conditions of a city in Myanmar. This calculation includes three aspects. Firstly, the maximum solar energy availability for the flat plate solar collector tilted at the optimum angle was estimated. Secondly, the convective heat transfer coefficient of nanofluid was calculated as a function of volume concentration and size of the nanoparticle. Thirdly, the overall heat loss coefficient of the flat plate solar collector was calculated using a method of iteration. Through these calculations, the collector efficiency was obtained as a function of volume concentration and size of the nanoparticle. The results showed increasing in collector efficiency by increasing the volume concentration up to 2% while the effect of nanoparticle size on the efficiency was marginal. The use of the CuO-water nanofluid as a working fluid could improve the efficiency of flat plate solar collector up to 5% compared with water as a working fluid under the same ambient, radiant and operating conditions.